Preparation and characterization of 2Na3SbS4·Na2WS4 and 2Na3SbS4·Na4XS4 (X = Si, Ge, Sn) glass–ceramic electrolytes. Issue 5 (9th January 2023) - Liang, Bo; Wang, Guoda; Shan, Haiyang; Dong, Pingping; Yu, Liangliang; Lin, Changgui; Gao, Chengwei; Liu, Yongxing; Shen, Xiang; Jiao, Qing
Abstract: Solid Na‐ion‐conducting sulfides exhibited potential applications for commercial solid‐state rechargeable batteries because of their low cost and good contact with the electrode. In the present work, a sulfide sodium‐ion conductor 2Na3 SbS4 ·Na2 WS4 with a conductivity of 1.55 mS cm −1 was obtained, which was identified as superior to the 2Na3 SbS4 ·Na4 XS4 (X = Si, Ge, Sn) systems. Further exploration of the heat treatment to improve the crystallinity of the glass resulted in a high conductivity of 1.9 mS cm −1 and low activation energy of 0.24 eV for the 2Na3 SbS4 ·Na2 WS4 glass–ceramic electrolyte. The high crystallinity after heat treatment at 380°C facilitated the migration of Na + together with large sodium vacancies formed by doping with W 6+ in 2Na3 SbS4 ·Na2 WS4 glass–ceramic electrolyte, resulting in the improved electrochemical performance. In addition, the air stability of the 2Na3 SbS4 ·Na2 WS4 glass–ceramic electrolyte decreased monotonically with increase of the annealing temperature, and heat application at 380°C effectively improved the electrolyte tolerance to the air compared with pure Na3 PS4 electrolyte. The origins of aliovalent ion doping and thermal effect on the electrochemical performance were discussed in detail.